2021
DOI: 10.3390/antib10020015
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for the Nonclinical Safety Evaluation of Antibody–Drug Conjugates

Abstract: The targeted delivery of drugs by means of linking them to antibodies (Abs) to form antibody–drug conjugates (ADCs) has become an important approach in oncology and could potentially be used in other therapeutic areas. Targeted therapy is aimed at improving clinical efficacy while minimizing adverse reactions. The nonclinical safety assessment of ADCs presents several unique challenges involving the need to examine a complex molecule, each component of which can contribute to the effects observed, in appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…During the different stages of their development and optimization, the in vivo evaluation of ADCs in preclinical models constitutes an essential step allowing the selection of the best candidates susceptible to be transferred to further clinical studies. In this respect, the half-life and blood stability of the construct, the premature release of the drug, and the amount of antibody and drug components accumulated within the target and nontarget tissues are key elements that have to be carefully considered, all of them being directly related to efficacy and safety of the conjugates . Because of their dual nature, determining the in vivo fate of both ADC components may turn out to be challenging and requires the use of multiple and complementary bioanalytical approaches .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the different stages of their development and optimization, the in vivo evaluation of ADCs in preclinical models constitutes an essential step allowing the selection of the best candidates susceptible to be transferred to further clinical studies. In this respect, the half-life and blood stability of the construct, the premature release of the drug, and the amount of antibody and drug components accumulated within the target and nontarget tissues are key elements that have to be carefully considered, all of them being directly related to efficacy and safety of the conjugates . Because of their dual nature, determining the in vivo fate of both ADC components may turn out to be challenging and requires the use of multiple and complementary bioanalytical approaches .…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the half-life and blood stability of the construct, the premature release of the drug, and the amount of antibody and drug components accumulated within the target and nontarget tissues are key elements that have to be carefully considered, all of them being directly related to efficacy and safety of the conjugates. 7 Because of their dual nature, determining the in vivo fate of both ADC components may turn out to be challenging and requires the use of multiple and complementary bioanalytical approaches. 8 In addition to this first level of complexity, conventional ADCs are often heterogeneous mixtures of chemically distinct molecules varying in terms of DAR and conjugation sites, which can furthermore evolve in vivo upon various biological parameters.…”
Section: ■ Introductionmentioning
confidence: 99%
“…MMAE was selected as a payload for ADC conjugation as its clinical efficacy and toxicity profiles have been well established with several approved ADCs (i.e., brentuximab vedotin, polatuzumab vedotin, enfortumab vedotin). Due to the absent expression of CLDN6 in normal tissue, clinical toxicities beyond those previously reported for MMAE-containing ADCs such as peripheral neuropathy, hematologic toxicities, hepatotoxicity, myelosuppression, ocular disorders, and skin reactions, are not expected ( 46, 47 ). In vivo studies confirmed that CLDN6–23-ADC inhibited the growth of CLDN6 expressing UMUC4 xenograft models with much greater efficacy than was observed with the unconjugated antibody, CLDN6–23-mAb.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody-Drug Conjugates (ADCs) are among the fastest growing drug modalities. 1,2 ADCs combine monoclonal antibodies (mAbs) generally targeting specific antigens, such as cancer tissues, with cytotoxic payloads [3][4][5] and have led to significantly increased survival rates for cancer patients. 6,7 For process development of ADCs, the cytotoxic nature of the linker/payloads (LPs) is a challenge.…”
Section: Introductionmentioning
confidence: 99%